Analisis Produktivitas Dan Efisiensi Industri Di Propinsi Jawa Tengah - Tri Wahyu (Fakultas Ekonomika dan Bisnis UNTAG Semarang, 2011)
AbstractDevelopment in the industrial sector is the main priority of economic development, without ignoring the development in the other sectors. Industrial processing sector has a dominant role in national economic. During the last five years the growth of the industrial sector actually is not as fast as expected. Before the occurrences of the economic crisis in 1997, the industrial sector is able to grow two digit growths and is always on the GDP growth. After the crisis, the industrial sector growth slowed, and less than 5 percent per year. This research is trying to do a study on how productivity and efficiency of the industrial sector to take an object of research industry sector are in the provinces of central java with the period from the year 2000 -2005. Based on the result of the known fact that the productivity growth of the industrial sector are in large-middle in central java is still below the 0.02 percent per year. While the level of efficiency the industrial sector, are in central java during the period of observation can be said not yet efficient. During the years 2000 – 2005 the industry had not reached the industrial sector is efficient with KKI 18 clothing industry that is so. The low level of efficiency in the industrial sector achieved with KKI 31 industry, namely electricity and equipment, the efficiency 34,51 in 2000. There are 6 (six) of the industrial sector achieve efficient in the last three years the period of observation: industry KKK with 15, 16, 17, 24, 34 and 35; food & beverages, tobacco, textiles, chemical & chemical goods, vehicles and other transportation equipment. Keywords : KKI, Productivity, Efficiency, and Industry Sector